2002
DOI: 10.2139/ssrn.1088793
|View full text |Cite
|
Sign up to set email alerts
|

Wealth Shocks and Retirement Timing: Evidence from the Nineties

Abstract: This paper explores whether the timing of retirement responds to unexpected changes in wealth. Although the normality of leisure is a standard assumption in economic models, econometric support for it has not been consistent. The period of the 1990s allows a reexamination of this question because of the large and unexpected capital gains realized by many households. Using the 1992 to 1998 waves of the Health and Retirement Study, and two different identification strategies, I find evidence consistent with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 32 publications
(39 reference statements)
0
36
0
Order By: Relevance
“…al., 2006). For instance, Farber (2008) found that job loss among older workers has long-lasting negative consequences for employment and wages (Chan and Stevens 1999, 2001von Wachter, 2007). Chan and Stevens (1999) estimate that the employment rate of displaced older workers two years after a job loss is 25 percentage points lower than that of similar non-displaced workers and that the median reemployed worker earns 20 percent less than at his old job.…”
Section: Labor Market Shocksmentioning
confidence: 99%
“…al., 2006). For instance, Farber (2008) found that job loss among older workers has long-lasting negative consequences for employment and wages (Chan and Stevens 1999, 2001von Wachter, 2007). Chan and Stevens (1999) estimate that the employment rate of displaced older workers two years after a job loss is 25 percentage points lower than that of similar non-displaced workers and that the median reemployed worker earns 20 percent less than at his old job.…”
Section: Labor Market Shocksmentioning
confidence: 99%
“…Even when authors use similar sources of wealth variation, the prior literature finds contrasting evidence. For example, Coronado and Perozek (2003) and Sevak (2001) find that unanticipated stock market gains led workers to retire earlier, while Coile and Levine (2006) find no effect of stock market fluctuations on retirement.…”
Section: Ambiguity In the Previous Literaturementioning
confidence: 99%
“…In a study that tested wealth shocks on retirement timing, Sevak (2002) This has not yet been examined in the literature" (pg. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Sevak (2002) showed that workers in the 1990s reacted to the positive wealth shocks by retiring earlier. Arriving at the same conclusion, Coronado and Perozek (2001) also proposed that the likely cause of the delay in retirement among workers following the 1990s was the poor equity performance.…”
Section: T: Current Time;mentioning
confidence: 99%